The role of LGU in post earthquake adaptation the case of Ormoc City. - Ablen, Margaret P.; Brazas-Lim, Ladylyn (Margaret P. Ablen, 2018)
On July 6, 2017, a 6.5 magnitude earthquake shook Ormoc City, destroying infrastructure and houses, and displacing hundreds of families. Two barangays have experienced the brunt of the damage, namely Lake Danao and Tongonan, wherein 499 and 629 families were affected, respectively (OCDSWDO, 2017). In nearly a year, displaced persons due to the quake are still living in emergency shelters, with assistance seizing in only three months after the said disaster. In line with their situation, this research was aimed to document the adaptive strategies used by the uprooted people, as well as to determine the local government's assistance after the earthquake. Finally, the study will analyze whether the actions done by the government facilitated or hindered the adaptation of the earthquake-hit people. Using a qualitative method in gathering data, the research has found that centralization of assistance, lack of longterm recovery planning, and limited resources of the Ormoc City-LGU has deterred the adaptation of its constituents after the 6.5 magnitude earthquake, and prompted them to adjust to their situation on their own, with little contribution from the LGU. Focus on respective sector assistance such as health, housing, and livelihood, are recommended for further studies, as well as improvements in the part of local governments in assisting the people for them to be able to adapt and eventually recover from the effects of the disaster.
A research paper (B.A.S.S. Political Science) -- University of the Philippines, Tacloban.